Help-seeking behavior and self-medication of a population in an urban area in Turkey: cross sectional study - (:unkn) unknown (My University, 2000)
AIM: To define help-seeking behavior and self-medication among people with different symptoms and complaints in an industrialized urban area of Turkey. METHODS: This cross-sectional study was carried out in the city center of Kocaeli province, Western Turkey, in October-November 1998. To research help-seeking behavior in respect of secondary prevention and curative practices, we randomly selected households (N=812), interviewed the household members at their home, and recorded the reasons for visiting a pharmacy in 6 pharmacies (N=1,331 visits to pharmacy) in the Kocaeli region. RESULTS: The majority of interviewed people knew the meaning and importance of regular medical checkups, and only 7% had never underwent periodic checkups, mainly because of the lack of interest or time. Self-medication was found to be the dominant mode of help-seeking behavior, especially in the case of pain. The proportion of unprescribed to prescribed drugs was 1:1.75, with analgetics, antipyretics, expectorants, and antitussives as the most commonly requested unprescribed drugs. CONCLUSION: A considerable amount of health care occured within the popular sector, with self-medication and pharmacist's advice as dominant modes of behavior. The health care system should take this into account when planning activities aimed at detection of disease.
Keywords: Adult; Female; Humans; Middle Aged; Turkey; Cross-Sectional Studies; Male; Interviews as Topic; Chi-Square Distribution; Urban Population; Medically Underserved Area; Patient Acceptance of Health Care; Pharmaceutical Services; Sampling Studies; Self Medication